The effect of Diazepam in pain reduction following mandibular impacted third molar surgery - Daneshvar M.E (Tehran University of Medical Sciences, 2004)
Pain control is of high importance in dentistry. Prescribing sedatives such a"nDiazepam, as an anti-depressant and pain threshold elevator drug is able to influence the patient's reaction to"npain and reduce it."nPurpose: The aim of the current study was to evaluate the effect of Diazepam in pain reduction following"nmandibular impacted third molar surgery."nMaterials and Methods: In this study, which was conducted in the department of Oral and Maxillofacial"nsurgery Faculty of Dentistry, Tehran University of Medical sciences. The patients were divided into two equal"ngroups (n=30). For controls, antibiotics and analgesics were prescribed after surgery. However, except the"naforementioned drugs, Diazepam (5mg), three times per day, was prescribed for the experimental group. The"namount of mouth opening was also measured as an auxiliary sign after one week. The data were compared by"nX2 test after one week."nResults: 60% of the experimental group and 13.8% of the control group felt a weak pain. Statistically"nsignificant differences were observed regarding pain feeling between two groups (P<0.001). Severe pain"nfeeling was 34.5% and 10%, for control and experimental groups, respectively."nConclusion: It is suggested that Diazepam is an effective pain reduction drug following third molar surgery."nThis drug has also a relative effect on temporary trismus resulting probably from muscle trauma or pain.